1998
DOI: 10.1029/98wr02521
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and physical factors that influence the homogeneity of regional floods in southeastern Australia

Abstract: The identification of hydrologically “homogeneous” regions is a primary step in many regional flood frequency techniques. Although statistical procedures for identifying homogeneous regions abound in the literature, there has been relatively little effort directed toward the identification of the physical and climatic basin characteristics that cause similarity in standardized flood peak distributions. We use regional flood peak and basin characteristics data for 104 basins in southeastern Australia to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Many RFFA methods have been developed and tested for different countries in the world (e.g. Cunnane, 1988;Hosking and Wallis, 1993;Zrinji and Burn, 1994;Bates et al, 1998;Pandey and Nguyen, 1999;Ouarda et al, 2001;Merz and Blöschl, 2005;Micevski and Kuczera, 2009;Gaume et al, 2010). Some of the most commonly adopted RFFA methods in practice include the index flood method (Dalrymple, 1960;Hosking and Wallis, 1993), rational method (Mulvany, 1851;I.…”
Section: Introductionmentioning
confidence: 99%
“…Many RFFA methods have been developed and tested for different countries in the world (e.g. Cunnane, 1988;Hosking and Wallis, 1993;Zrinji and Burn, 1994;Bates et al, 1998;Pandey and Nguyen, 1999;Ouarda et al, 2001;Merz and Blöschl, 2005;Micevski and Kuczera, 2009;Gaume et al, 2010). Some of the most commonly adopted RFFA methods in practice include the index flood method (Dalrymple, 1960;Hosking and Wallis, 1993), rational method (Mulvany, 1851;I.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the Generalised Extreme Value (GEV) and Wakeby distributions provide the best approximation to flood flow data in the regions of Australia that are dominated by rainfall during the winter months. Bates et al (1998) adopted the method of L moments in identifying homogeneous regions in the context of regional flood frequency analysis for south-east Australia. Haddad and Rahman (2008) compared a number of distributions and parameter estimation procedures for 18 catchments in south-east Australia and found that the GEV distribution provided the best fit to the selected data set.…”
Section: Introductionmentioning
confidence: 99%
“…In hydrological applications the site characteristics would typically include geographical location of the site or other physical properties such as watershed area and slope, associated with the site (e.g. Bates et al 1998;Chiang et al 2002). For AMDSL time series, the latitude and longitude of the stations are considered as the site characteristics.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…These techniques include multivariate statistics such as regression, hierarchical cluster and principal component analyses (e.g. Bates et al 1998;Chiang et al 2002;Modarres 2006), region of influence (Burn 1990) and canonical correlation analysis (Cavadias et al 2001).…”
Section: Introductionmentioning
confidence: 99%